Pelaksanaan Pemberian Bonus Terhadap Pekerja Tetap Dan Pekerja Kontrak Berdasarkan Peraturan Pemerintah Nomor 36 Tahun 2021 Dan Perjanjian Kerja Bersama (PKB) Di PT. Kemas Indah Maju - Putra Fahrezi, Daffa; Nira Sasvia, Thasya; Putri Azzahra, Nhazwa; Wahyuningsih, Fitria; Silitonga, Esra Ellis Maryati (Journal of Industrial Relations Studies, 2025)
This study aims to analyze the implementation of giving bonuses to permanent workers and contract workers at PT Kemas Indah Maju based on Government Regulation (PP) No. 36 of 2021 and the Collective Labor Agreement (PKB). The method used in this research is empirical with interview, observation, and documentation techniques. In the context of intense industrial competition, employee welfare is an important factor to increase productivity and loyalty. However, this study found that since 2020, PT Kemas Indah Maju has not provided bonuses to its employees, even though this has been regulated in the PKB. Lack of transparency regarding company profits and worker dissatisfaction are the main issues faced. The labor union has played an active role in fighting for workers' rights regarding bonuses, but no agreement has been reached. This study concludes that companies need to comply with existing regulations and establish good communication with workers to improve welfare and productivity. It is suggested that companies provide clear and open financial reports to workers and conduct periodic evaluations of bonus policies